Overview on Phyto-based Treatment for Anxiety - Alambayan, Jyoti; Garg, Vandana (Current Psychopharmacology, 2020)
Background: The prevalence of psychiatric disorders, such as anxiety, is very common and affects many people all around the world. Currently, many synthetic pharmacological products/ drugs are available in the market to cure the disorder but associated with various adverse reactions or side effects, which may cause discomfort and sometimes other disorders to the patients. In the past years, the use of complementary and alternative medicine has increased. The exploration in the area of herbal psychopharmacology has received much attention as people are using more herbal treatment to benefit their health. Objective: To provide comprehensive information on anxiety disorder and its herbal treatment. Methods: In this review, we enlisted the plants, plant extracts and isolated components (if any) along with models used to explore anxiolytic property; in retrospect, still a lot of research required to establish them clinically. Result: Literature revealed that a variety of medicinal plants are effective for the treatment of anxiety like Ginkgo biloba, Passiflora incarnata, Gelsemium sempervirens, Piper methysticum, Bauhinia variegate, Matricaria recutita, Brassica oleracea, Hypericum perforatum, Echium amoenum, and Scutellaria lateriflora. Conclusion: Exploration of herbal plants may be beneficial to establish more potential compounds for the treatment of anxiety disorders.
Keywords: review